Rise of Central Conservatism in Political Leadership: Erbakan’s National Outlook Movement and the 1997 Military Coup in Turkey - Temiz, Suleyman (Intellectual discourse, 2018)
In democratic countries such as Turkey, political parties are established around charismatic leaders and these leaders stay at the centre of the party, from naming the party to the arrangement of deputy candidates. National Outlook, a movement which prevailed in Turkish politics for forty years, won its biggest victory and formed a coalition government in 1995 with the True Path Party, under the leadership of Tansu Ciller. Having secularized its legal system in the early years of the Republic, successive regimes in Turkey aggressively westernized all aspects of life. However, during the multiparty period, the style of radical secularism in Turkey was opposed by conservative groups and it has been criticized since then. The relationship between civil society and the military has always been problematic in Turkey, as the Turkish Army has always been suspicious of conservative governments on the issue of secularism. On several occasions the military has intervened in politics in order to prevent Islam from impinging on the Republic’s secular identity, and it expected to continue in its role as the champion of secularism when the Justice and Development Party (AKP) came to power in November 2002. For the Turkish military, the National Outlook Movement is more dangerous than Kurdish separatist terrorism, being labelled irtica. The paper provides insights into the Turkish political context for the decision and analyses the roles of key actors in Turkish politics, such as Government and Army, during the 28 February 1997 process, their motivations and the policy processes in the country.